2022
DOI: 10.1007/s10924-022-02682-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Removal of Cationic Crystal Violet and Anionic Reactive Yellow Dyes using eco-friendly Chitosan Functionalized by Talc and Cloisite 30B

Abstract: Designing adsorbent materials that can effectively remove many types of organic dyes is crucial because of the wide diversity of synthetic dyes found in wastewater. Thus, this study presents the synthesis of economic and eco-friendly adsorbent composites composed of chitosan (Cs), talc (T), and Cloisite 30B clay (C) to remove both cationic crystal violet (CV) and anionic reactive yellow 145 (RY) dyes for the first time. Cs was functionalized with T and subsequently the CsTC1 and CsTC2 composites were prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…43 The composite formation took place as a result of interactions between OH groups on the surface of the NCC and OH and/or NH 2 groups on Chitosan. 38 Similarly, the peaks at 898 and 1630 cm −1 corresponding to the β-glycosidic linkage between glucose unit in cellulose and OH bending in the NCC spectra were shifted to 877 and 1654 cm −1 in NCC–CH spectra with increased intensity. The shifted peak at 1654 cm −1 and the appearance of new peak at 1561 cm −1 (–NH group) in the NCC–CH spectra could be due to the presence of type I and type II amide groups in the chitosan molecule.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…43 The composite formation took place as a result of interactions between OH groups on the surface of the NCC and OH and/or NH 2 groups on Chitosan. 38 Similarly, the peaks at 898 and 1630 cm −1 corresponding to the β-glycosidic linkage between glucose unit in cellulose and OH bending in the NCC spectra were shifted to 877 and 1654 cm −1 in NCC–CH spectra with increased intensity. The shifted peak at 1654 cm −1 and the appearance of new peak at 1561 cm −1 (–NH group) in the NCC–CH spectra could be due to the presence of type I and type II amide groups in the chitosan molecule.…”
Section: Resultsmentioning
confidence: 95%
“…Consequently, this can improve the bead's ability to adsorb dyes on its surface. 38 The swelling property of hydrogels is one of its key properties, which is very important for the practical application of hydrogels. Swelling ratio (SR) is controlled by the porosity and chemical functionality of the adsorbent.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the FTIR spectrum of CS with that of FE/AS/CS composite, it was observed that the characteristic vibration bands for CS were observed in both spectra besides the emergence of new bands in the spectrum of FE/AS/CS composite. The main characteristic bands of CS that were observed in both spectra were at 3393 cm −1 (for N-H and O-H stretching), 1573 cm −1 (due to N-H bending) and 1009 cm −1 (for C-O stretching) [54], while the new bands that were observed in the spectrum of FE/AS/CS composite were at 3688 cm [55]. Since the characteristic vibration bands for CS, AS and FE were observed in the spectrum of FE/AS/CS composite, this indicates that the AS and FE were successfully combined with CS matrix.…”
Section: Characterization Of Fe/as/cs Compositementioning
confidence: 96%
“…[ 21 ] Various types of clay‐filled polymer composites have been fabricated in the literature for water treatment like the development of amido‐functionalized carboxymethyl chitosan montmorillonite composite for the removal of Hg (II) [ 25 ] ; nanoclay/poly (vinyl alcohol) (PVA)/polysulfone (PSf) nanocomposite membrane for pharmaceuticals removal [ 26 ] ; poly (acrylamide ‐co‐ 2‐ acrylamido‐2‐methylpropane sulfonic acid)/Na‐MMT hydrogel nanocomposite for dyes removal [ 27 ] ; clay/poly N‐isopropylacrylamide (PNIPAm) nanocomposite hydrogels for adsorption of crystal violet [ 28 ] ; starch‐montmorillonite/polyaniline (St‐MMT/PANI) nanocomposite for the removal of reactive blue (RB 194) [ 29 ] ; styrene/acrylic acid/organophilic montmorillonite hybrid nanocomposite hydrogel for the removal of anionic(acid green B) and cationic (maxilon C.I. basic) dyes [ 30 ] ; Chitosan/Talc/Cloisite 30B hybrid composites for the removal of cationic crystal violet and anionic reactive yellow dyes [ 31 ] ; and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…C30B is a type of MMT modified with quaternary ammonium salts (methyl tallow bis‐2‐hydroxyethyl ammonium) and was used here as it contains an abundance of hydroxyl groups, which would be expected to increase the adsorption affinity of CA film toward cationic dyes. [ 31 ] The surface of C30B was further modified here by grafting it with a functionalized polymer (polyacrylic acid) using reversible addition‐fragmentation chain transfer (RAFT) polymerization technique. The objective of this modification was to generate a large number of reactive sites (carboxylate groups) on the C30B surface so that more cationic dye molecules could be adsorbed.…”
Section: Introductionmentioning
confidence: 99%